2017
DOI: 10.5116/ijme.59ba.2d47
|View full text |Cite
|
Sign up to set email alerts
|

A review of antimicrobial stewardship training in medical education

Abstract: ObjectivesWe reviewed the published literature on antimicrobial stewardship training in undergraduate and postgraduate medical education to determine which interventions have been implemented, the extent to which they have been evaluated, and to understand which are most effective. MethodsWe searched Ovid MEDLINE and EMBASE from inception to December 2016. Four thousand three hundred eighty-five (4385) articles were identified and underwent title and abstract review. Only those articles that addressed antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 66 publications
0
43
0
2
Order By: Relevance
“…This method, suggested by the WHO [34] has successfully been applied in different countries such as Nepal [35] and Japan [36]. Similarly, Silverberg et al [37] conducted a review of recent literature in which they identified 48 articles, distributed worldwide, with different teaching methodologies on antibiotic administration in undergraduate and postgraduate medical education, and although that study showed that medical schools worldwide are implementing interventions on this topic, a rigorous evaluation of interventions is required to determine if such efforts have indeed been effective. Such interventions and evaluation could provide a basis on which to focus micro-and macrocurricular academic changes for local universities.…”
Section: Discussionmentioning
confidence: 99%
“…This method, suggested by the WHO [34] has successfully been applied in different countries such as Nepal [35] and Japan [36]. Similarly, Silverberg et al [37] conducted a review of recent literature in which they identified 48 articles, distributed worldwide, with different teaching methodologies on antibiotic administration in undergraduate and postgraduate medical education, and although that study showed that medical schools worldwide are implementing interventions on this topic, a rigorous evaluation of interventions is required to determine if such efforts have indeed been effective. Such interventions and evaluation could provide a basis on which to focus micro-and macrocurricular academic changes for local universities.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals (HCPs) working in hospitals should have adequate knowledge and awareness of AMR, its triggering factors, and strategies required to cope with AMR (Labi et al, 2018;Nicholson et al, 2018;Hayat et al, 2019a;Kalungia et al, 2019). Different professionals will have different views which could affect the functioning of hospital ASPs (Venugopalan et al, 2016;Salsgiver et al, 2018). Furthermore, the success of implementing ASPs in hospitals is highly dependent on the joint efforts of HCPs, including ID physicians, pharmacists, and nurses.…”
Section: Introductionmentioning
confidence: 99%
“…This method, suggested by the WHO [34] has successfully been applied in different countries such as Nepal [35] and Japan [36]. Similarly, Silverberg et al [37] conducted a review of recent literature in which they identified 48 articles, distributed worldwide, with different teaching methodologies on antibiotic administration in undergraduate and postgraduate medical education, and although that study showed that medical schools worldwide are implementing interventions on this topic, a rigorous evaluation of interventions is required to determine if such efforts have indeed been effective. Such interventions and evaluation could provide a basis on which to focus micro-and macro-curricular academic changes for local universities.…”
Section: Discussionmentioning
confidence: 99%